Morfologia matemática aplicada à detecção de sombras e nuvens em imagens de alta resolução - Statella, Thiago; Silva, Erivaldo Antonio da [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2008)
The spatial resolution improvement of orbital sensors has broadened considerably the applicability of their images in solving urban areas problems. But as the spatial resolution improves, the shadows become even a more serious problem especially when detailed information (under the shadows) is required. Besides those shadows caused by buildings and houses, clouds projected shadows are likely to occur. In this case there is information occlusion by the cloud in association with low illumination and contrast areas caused by the cloud shadow on the ground. Thus, it's important to use efficient methods to detect shadows and clouds areas in digital images taking in count that these areas care for especial processing. This paper proposes the application of Mathematical Morphology (MM) in shadow and clouds detection. Two parts of a panchromatic QuickBird image of Cuiab-MT urban area were used. The proposed method takes advantage of the fact that shadows (low intensity - dark areas) and clouds (high intensity - bright areas) represent the bottom and top, respectively, of the image as it is thought to be a topographic surface. This characteristic allowed MM area opening and closing operations to be applied to reduce or eliminate the bottom and top of the topographic surface.

A evolução da resolução espacial dos sensores orbitais aumentou consideravelmente a aplicação de suas imagens na solução de problemas em áreas urbanas, mas, com o incremento da resolução espacial, a presença de sombras se torna um problema grave à medida que informações detalhadas da cena (sob sombras) sejam necessárias. Além das sombras inerentes ás feições do terreno, sombras projetadas por nuvens podem ocorrer. Nesse caso, além das áreas de baixa iluminação e contraste causadas pela projeção da sombra sobre a superfície, há também a oclusão de informações por parte da nuvem. Portanto é importante o uso de métodos eficientes que detectem as sombras e nuvens em imagens digitais tendo em vista que estas áreas necessitam de processamentos especiais. Este trabalho propõe a utilização de Morfologia Matemática (MM) na execução dessa tarefa. Duas seções de uma imagem QuickBird pancromática da área urbana da cidade de Cuiabá-MT foram adotadas como áreas de estudo. O método proposto tira vantagem do fato de as sombras e nuvens representarem vales e picos de intensidade na imagem quando esta é representada como uma superfície topográfica. Aproveitando-se dessa característica, operações de abertura e fechamento de área foram aplicadas para reduzir ou eliminar, respectivamente, picos e vales.
Mathematical morphology applied to shadows and clouds detection in high resolution images
Keywords: Mathematical Morphology; Shadows detection; Cloud Detection; High Resolution Imagery